Literature Review on the Relationship Between Taxation and Social Welfare Across Various Countries - Nofitasari, Susi; Putri, Risa Haruman (Global Journal of Taxation and Fiscal Policy, 2025)
This study analyzed the relationship between taxation and social welfare in various countries by conducting a systematic literature review. The research aims to identify key factors influencing tax compliance and the role of taxation in income redistribution and welfare financing. The study adopts a qualitative approach by analyzing academic literature, policy reports, and empirical findings from reputable sources. The results indicate that progressive taxation significantly contributes to social welfare enhancement in high-income countries, whereas developing nations face challenges such as low tax compliance and administrative inefficiencies. The findings highlight the importance of tax education, digital taxation systems, and transparent policies in improving compliance and maximizing welfare benefits. Moreover, the study underscores the need for inclusive tax reforms that ensure fair distribution of tax burdens while optimizing revenue allocation for public services. Policymakers should focus on strengthening institutional frameworks, enhancing technological adoption, and fostering public trust to improve the effectiveness of taxation in supporting social welfare. This research provides in-depth insights into global taxation trends and policy recommendations for developing more equitable and efficient tax systems.